O lazer dos professores de educação física de Miracema do Tocantins e região em meio à pandemia da Covid-19 - Teixeira, David Rodrigues (Universidade Federal do Tocantins, 2023)
The 7er mis7 work has as theme: The leisure of Physical Education teachers from Miracema do Tocantins and region in the midst of the COVID-19 pandemic. With the general objective: to discover what Physical Education teachers from Miracema do Tocantins and region do to maintain a leisure routine during the COVID-19 pandemic. Based on this objective, we describe brief notes about leisure and the covid-19 pandemic and how this disease has impacted the leisure practices of Physical Education teachers. The study was carried out remotely using an online questionnaire, prepared through google forms. Participants were Physical Education teachers from the cities of Miracema, Lajeado, Tocantínia and Miranorte, all located in the state of Tocantins. Of the 25 teachers who participated in the survey, only 12 answered the questionnaire correctly, leaving no answer blank. It is considered that the pandemic has changed leisure habits on the 7er mis teachers, as many of them cite covid-19 as an obstacle to the continuity of leisure activities, therefore, a careful look at the possible effects that the pandemic may have on long 7er mis necessary.